Durum wheat seedling responses to simultaneous high light and salinity involve a fine reconfiguration of amino acids and carbohydrate metabolism. Issue 3 (19th October 2016) - Woodrow, Pasqualina; Ciarmiello, Loredana F.; Annunziata, Maria Grazia; Pacifico, Severina; Iannuzzi, Federica; Mirto, Antonio; D'Amelia, Luisa; Dell'Aversana, Emilia; Piccolella, Simona; Fuggi, Amodio; Carillo, Petronia
Abstract : Durum wheat plants are extremely sensitive to drought and salinity during seedling and early development stages. Their responses to stresses have been extensively studied to provide new metabolic targets and improving the tolerance to adverse environments. Most of these studies have been performed in growth chambers under low light [300–350 µmol m −2 s −1 photosynthetically active radiation (PAR), LL]. However, in nature plants have to face frequent fluctuations of light intensities that often exceed their photosynthetic capacity (900–2000 µmol m −2 s −1 ). In this study we investigated the physiological and metabolic changes potentially involved in osmotic adjustment and antioxidant defense in durum wheat seedlings under high light (HL) and salinity. The combined application of the two stresses decreased the water potential and stomatal conductance without reducing the photosynthetic efficiency of the plants. Glycine betaine (GB) synthesis was inhibited, proline and glutamate content decreased, while γ‐aminobutyric acid (GABA), amides and minor amino acids increased. The expression level and enzymatic activities of Δ1‐pyrroline‐5‐carboxylate synthetase, asparagine synthetase and glutamate decarboxylase, as well as other enzymatic activities of nitrogen and carbon metabolism, were analyzed. Antioxidant enzymes and metabolites were also considered. The results showed that the complex interplay seen in durum wheat plants under salinity at LL was simplified: GB and antioxidants did not play a main role. On the contrary, the fine tuning of few specific primary metabolites (GABA, amides, minor amino acids and hexoses) remodeled metabolism and defense processes, playing a key role in the response to simultaneous stresses.